2013
DOI: 10.5713/ajas.2012.12556
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Restricted Grazing Time on the Foraging Behavior and Movement of Tan Sheep Grazed on Desert Steppe

Abstract: To investigate the effect of restricted grazing time on behavior of Tan sheep on desert steppe, forty 4-months old male Tan sheep with an original body weight (BW) of 15.62±0.33 kg were randomly allocated to 4 grazing groups which corresponded to 4 different restricted grazing time treatments of 2 h/d (G2), 4 h/d (G4), 8 h/d (G8) and 12 h/d (G12) access to pasture. The restricted grazing times had a significant impact on intake time, resting time, ruminating time, bite rate and movement. As the grazing time de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
3
14
1
1
Order By: Relevance
“…These findings are consistent with the findings of several studies conducted on domestic ruminants elsewhere (Smith, 1961;Bayer, 1986;Ayantunde et al, 2000b;Kristensen et al, 2007;Moyo et al, 2012;Chen et al, 2013). Increased focus on grazing by daytime-only foraging cattle is necessary if they are to offset decreased forage intake due to restricted foraging time.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with the findings of several studies conducted on domestic ruminants elsewhere (Smith, 1961;Bayer, 1986;Ayantunde et al, 2000b;Kristensen et al, 2007;Moyo et al, 2012;Chen et al, 2013). Increased focus on grazing by daytime-only foraging cattle is necessary if they are to offset decreased forage intake due to restricted foraging time.…”
Section: Discussionsupporting
confidence: 91%
“…Dairy cows can modify their intake rates in response to a constraint of access to pastures to maintain their intake and nutrient supply ( Perez-Ramirez et al, 2008 ). In previous studies, we detected that lambs under shorter grazing time systems always had higher pasture intake rates and higher intake time percentages during grazing ( Chen et al, 2013 ; Zhang et al, 2014 ). Lambs must improve their efficiency of grazing activities to consume more fresh pasture in a limited time.…”
Section: Discussionmentioning
confidence: 83%
“…The effects of restricted grazing time systems on the pasture intake, milk production and grazing behavior of dairy cows ( Kristensen et al, 2007 ; Perez-Ramirez et al, 2008 ) and sheep ( de Renobales et al, 2012 ) have previously been studied. In our previous research, we examined restricted grazing time systems on the ingestive behavior, dry matter intake, weight gain and other performances of growing lambs ( Xu et al, 2011 ; Chen et al, 2013 ; Zhang et al, 2014 ) and on the grassland (unpublished data); these data showed that moderate grazing time with the proper concentrate is a better way to produce lamb meat when considering animal performance. Additionally, a very long lamb grazing time (12 h/d) significantly reduced the quality and productivity of the grassland compared to an area experiencing less grazing hours (<8 h/d), but there were no significant differences in the productivity of the grasslands in which lambs grazed for 2 h/d, 4 h/d, and even 8 h/d.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in continuously stocked lactating meat sheep grazing a temperate perennial grassland, the time devoted to grazing was 87% of access time in the ewes whose access to pasture was restricted to about 9 h d −1 , as compared to 52% of access time in the unrestricted counterparts (Iason et al ., ). Recent data on meat sheep (Chen et al ., ) and lambs (Zhang et al ., ) confirm this general trend.…”
Section: Discussionmentioning
confidence: 99%